Pengaruh Proactive Personality terhadap Public Service Motivation pada Aparatur Sipil Negara di Disdukcapil Kota Padang - Ersya, Miftahur Raihan; Mardianto, Mardianto (Lembaga Yasin AlSys, 2025)
Public services in Indonesia are still unsatisfactory. Based on the annual report of Ombudsman RI in 2023, it was reported that the number of public complaints received by Ombudsman RI was 7,392 cases. This public report is higher than previous years. Public services in Indonesia are carried out by the state civil apparatus. Individual factors in the state civil apparatus have an important role in predicting the performance of government organizations. One of these individual factors is public service motivation. This research focuses on assessing the influence of proactive personality on public service motivation in state civil apparatus in Disdukcapil Padang City. This type of research is quantitative with a survey. The sample was 41 state civil apparatus. Sampling applied saturated sampling technique. Data were collected using a public service motivation scale developed based on the aspects described by Perry and a proactive personality scale compiled by Seibert based on Bateman and Crant's theory. Data were processed using simple linear regression test. The results showed that proactive personality has a significant effect on public service motivation with an influence coefficient of 22.1% and the remaining 77.9% is influenced by other variables not examined in this research. Research on public service motivation and proactive personality is important to be the basis for developing better management strategies, including recruitment, training and employee development in public organizations.